Effect of intralesional injection of autologous platelet rich plasma in patterned hair loss - Rai, Priyam Bhaskar; Khushwaha, Pragya (International Journal of Research in Dermatology, 2020)
Background: Regenerative effects of platelet-rich plasma’s (PRP) are utilized in treating various dermatological conditions. The present study compared the efficacy of intradermal autologous PRP in various grades of patterned hair loss with topical minoxidil and finasteride. Methods: Patients with patterned hair loss were randomized to receive either minoxidil 5% in (male), 2% in (female) and finasteride 1 mg (only in male) or PRP in addition to the above treatment. A total of 6 sittings were given to PRP group patients at interval of 21 days each over a total period of 4 months. All patients were followed up for the first time after 21 days of initiating the treatment and then after four months of starting the treatment. Results: Baseline demographic and clinical characteristics were similar in both the treatment groups. When assessed at the second follow up, hair wash test, hair pull test, V/T ratio, yellow dot test, mean hair diameter and global photographic assessment were favourable in significantly higher proportion of patients in the PRP group as compared to non-PRP group. Five non-PRP patients (6.7%) perceived no change in hair fall as compared to none in the PRP group. None of the cases reported increase in hair fall. Adverse effects reported (itching, erectile dysfunction, decreased libido and dizziness) were similarly distributed among the patients in both the treatment groups. Conclusions: Minoxidil and finasteride form the backbone of patterned hair loss treatment; adding PRP can achieve clinically better results with minimal side effects.